The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1111/j.1476-5381.1994.tb17154.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the distribution and characteristics of tachykinin NK1 binding sites between human and guinea pig lung

Abstract: The distribution and characteristics of tachykinin NK, binding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…Although previous studies of NK-1 receptor localization in the normoxic lung have generated conflicting results, our findings are consistent with previous work suggesting that very few detectable NK-1 receptors are present in the normal distal lung in rats, guinea pigs, or humans (8,17,29).…”
Section: Discussionsupporting
confidence: 91%
“…Although previous studies of NK-1 receptor localization in the normoxic lung have generated conflicting results, our findings are consistent with previous work suggesting that very few detectable NK-1 receptors are present in the normal distal lung in rats, guinea pigs, or humans (8,17,29).…”
Section: Discussionsupporting
confidence: 91%
“…Nerves containing tachykinins and tachykininbinding sites exist in the esophagus as well as in the airways (18,40). Because the esophageal and pulmonary systems share a similar embryological origin, the foregut, it would not be surprising if they also shared a common nerve pathway.…”
mentioning
confidence: 99%
“…Autoradiographic studies have detected binding sites for substance P in airway smooth muscle in the rabbit ASTHMA MEDIATORS (Black et al 1990). However, little, if any, binding for substance P was detected in airway smooth muscle in man (Goldie 1990;Walsh et al 1994) even though binding sites for substance P have been reported in one study of human airway smooth muscle (Carstairs & Barnes 1986). Whether methodological differences can account for these discrepancies is unclear but would seem unlikely, given that substance P binding sites were clearly detected in the microvasculature and submucosal glands of humans (Goldie 1990;Walsh et al 1994).…”
Section: Sensory Neuropeptidesmentioning
confidence: 97%
“…However, little, if any, binding for substance P was detected in airway smooth muscle in man (Goldie 1990;Walsh et al 1994) even though binding sites for substance P have been reported in one study of human airway smooth muscle (Carstairs & Barnes 1986). Whether methodological differences can account for these discrepancies is unclear but would seem unlikely, given that substance P binding sites were clearly detected in the microvasculature and submucosal glands of humans (Goldie 1990;Walsh et al 1994). Functional studies have revealed that tachykinins contract human isolated bronchi via NK 2 -receptors (Naline et al 1989;Advenier et al 1992).…”
Section: Sensory Neuropeptidesmentioning
confidence: 97%